The Effect of Bintaro (Cerbera manghas) Plants Extract on The Development of Grower Worm Pests (Spodoptera litura) - Hidayati, Diyah Putri Anjar; Susilo, Achmadi; Haryanta, Dwi (Journal of Applied Plant Technology, 2025)
In order to reduce the use of inorganic pesticides which have been proven to pollute the environment and endanger consumers, it is necessary to develop pesticides from plant materials. This study aims to obtain and determine the effect of bintaro plant extract on the development of grower worm (Spodoptera litura). The treatments consisted of 4 combinations of bintaro organs (leaves, bark, fruit flesh, and seeds) and 5 combinations of extract concentrations (2.5%, 5.0%, 7.5%, 10.0%, and 12.5%) so that there are 20 combinations and one control is repeated three times. This research was conducted at the Merdeka University Surabaya laboratory from April to May 2020 using a Completely Randomized Design (CRD). The results showed that the extract of the bintaro plant had no significant effect on the instar development of the grower worm (Spodoptera litura). Bintaro plant extract had a significant effect on the mortality of grower worm (Spodoptera litura) on days 15 to 20, while on the development of life it had a significant effect on days 12 to 20.